Analysis of Patients’ Satisfaction With the Work of Family Medicine Teams at the Primary Healthcare Center in Banja Luka - Milojević, Dragan; Stanetić, Kosana; Savić, Suzana; Petrović, Verica (General Practice, 2024)
Introduction: The primary healthcare reform in Bosnia and Herzegovina began in 1999. The focus was on the introduction of family medicine, in comparison to the existing dispensary model of care based on the practice of general medicine. The reform is an ongoing process, and all changes are being implemented to improve patients’ satisfaction. Our objective is to analyze patients’ satisfaction and the impact of socio-demographic factors on patients’ satisfaction with the work of family medicine teams. Methods: This research is an observational and descriptive study conducted in family medicine clinics of the Primary Healthcare Centre in Banja Luka from February 1st to April 1st 2022. The data was gathered using the EUROPEP questionnaire which is a standardized instrument for the evaluation of patients’ satisfaction with primary healthcare, as well as a questionnaire with socio-demographic information. The study comprised 250 patients from family medicine clinics in the city, suburbs, and countryside. Results: The analysis of 250 questionnaires has provided answers to 23 questions in the EUROPEP instrument assessing four domains: doctor-patient relation X̅ (4.22) SD (0.85); medical care X̅ (4.32) SD (0.90); information and support X̅ (4.04) SD (0.94); and organization of services X̅ (3.81) SD (0.98). Socio-demographic and other patient characteristics greatly impact family medicine patients’ satisfaction with healthcare services. Conclusions: In general, the patients are satisfied with the care provided by the family medicine teams of the Primary Healthcare Centre in Banja Luka, and least satisfied with the organization of services. According to individual questions in the EUROPEP questionnaire, the patients are most unsatisfied with reaching their doctors by phone, receiving advice from them, spending a lot of time waiting in the waiting rooms, and scheduling their appointments.